1.Решите:
А) (а-5)(а-3) = a² - 3a - 5a + 15 = a² - 8a + 15
Б) (5х+4)(2х-1) = 10x² - 5x + 8x - 4 = 10x² + 3x - 4
В) (3р+2с)(2р+4с) = 6p² + 12pc + 4cp + 8c² = 6p² + 16pc + 8c²
Г) (b-2)(b²+2b-3) = b³ + 2b² - 3b - 2b² - 4b + 6 = b³ - 7b + 6
2. Рaзложите на множители:
А) х(х-у)+а(х-у) = (x-y)(x+a)
3. Упростите:
0,5х(4х⁴-1)(5х²+2) = (2x^5 - 0,5x)(5x² + 2) = 10x^7 + 4x^5 - 2,5x³ - x
4. Представьте многочлены в виде произведения:
А) 2а-ас-2с+с² = a(2 - c) - c(2 - c) = (a-c)(2-c)
B) bx+by-x-y-ax-ay = b(x + y) - (x + y) - a(x + y) = (x+y)(b-1-a)
2√3-5 - 11÷2√3-1 Пусть а= 2√3, тогда:
(a-5)(a-1) - 11÷a-1
( (a-5)(a-1) - 11 ) : (a-1) = (a^2-a-5a+5-11) : ( a-1) = (12-12√3-6) : 2√3-1 =
=6(2-2√3-1) : 2√3-1 = 6(1-2√3) : (1- 2√3) = 6
ответ: 6